Optimization of on‐site cellulase preparation for efficient hydrolysis of atmospheric glycerol organosolv pretreated wheat straw. Issue 8 (25th March 2018) - Sun, Fubao; Mukasekuru, Marie Rose; Tan, Ling; Ren, Junli; Huang, Zhenxing; Ren, Hongyan; Zhang, Zhanying
Abstract: BACKGROUND: The cost of using cellulase to effectively release fermentable sugars from lignocellulosic substrates is still a major impediment to development of the enzyme‐based 'biorefinery' industry. This study attempted to optimize a cellulase preparation from on‐site fermentation to efficiently hydrolyse atmospheric glycerol organosolv (AGO)‐pretreated wheat straw. RESULTS: Addition of Cu 2+, PEG10000, L‐ascorbic acid and trehalose in the fermentation medium significantly improved the cellulase production. Use of all the additives enabled enhancement to 45.5% of filter paper cellulase (FPA), 14.7% of β‐glucosidase (BG) and 32.4% of carboxymethyl cellulase (CMCase). With the on‐site production of crude cellulase, accessory enzymes (β‐glucosidase (BG), xylanase and lysozyme) and additives (tea saponin (TS) and cationic polyacrylamide (c‐PAM)) were found to facilitate the hydrolysis of AGO‐pretreated substrates effectively. The optimized cellulase mixture allowed 96% of enzymatic hydrolysis at 5 FPU g ‐1 for 48 h on addition of 11.5 U g ‐1 BG, 180 U g ‐1 xylanase, 45 U g ‐1 lysozyme, 10 mg g ‐1 TS and 2 mg g ‐1 C‐PAM, which was twice that of the crude cellulase broth. CONCLUSION: Cellulase customization for specific substrate hydrolysis with on‐site produced broth produced an efficient pathway to lower the enzyme cost in the ongoing lignocellulosic biorefining industry. © 2018 Society of Chemical Industry